2011
DOI: 10.1111/j.1742-481x.2011.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of run-in and treatment data in a wound outcomes registry: clinical impact of topical platelet-rich plasma gel on healing trajectory

Abstract: Randomised controlled trials in chronic wounds typically exclude patients with comorbidities and confounding factors. Well-designed observational studies can provide complementary clinical evidence that randomised trials cannot address. This study determined if wound care registry outcomes could be an alternative data source and if the results would be robust and valid. Changes in wound area and depth were hypothesised to be different between run-in therapies and platelet-rich plasma (AutoloGel™, Cytomedix, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…Dionyssiou et al supported the findings in accelerating the healing by PRP with the results of the histological study; according to which, the use of PRP as in our study contributed to the early appearance of granulation tissues, acceleration of epithelialisation, and stimulation of angiogenesis processes in wounds . PRP has proven itself in Kim et al and Carter et al studies showing the acceleration, proliferation, and migration of keratinocytes, and a significant reduction in the surface and depth of the wounds …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Dionyssiou et al supported the findings in accelerating the healing by PRP with the results of the histological study; according to which, the use of PRP as in our study contributed to the early appearance of granulation tissues, acceleration of epithelialisation, and stimulation of angiogenesis processes in wounds . PRP has proven itself in Kim et al and Carter et al studies showing the acceleration, proliferation, and migration of keratinocytes, and a significant reduction in the surface and depth of the wounds …”
Section: Discussionsupporting
confidence: 88%
“…There are a number of studies showing that the use of autologous PRP can improve the results of wound‐healing processes, as well as in cases of poorly healing wounds. Several controlled studies have given statistically significant evidence that the use of PRP leads to the acceleration of wound healing . There are three controlled studies on humans that reported of improvement of wound healing with regard to healing time, the quality of life, and reduction of pain .…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the application of aPRP gel directly to the wound site would increase the level of key growth factors, and thus speed the healing process. Studies and trials have compared aPRP gel to standard of care treatments, including debridement, topical antibiotic gel, and daily dressing changes [15][16][17]. A systematic review that included seven trials found inconclusive results for the role of aPRP in the complete healing of chronic skin ulcers (see Table 1) [18].…”
Section: Clinical Applications and Evidence For Efficacymentioning
confidence: 98%
“…This might be attributed to RCT designs that do not reflect the complex issues faced in clinical practice and are limited by the challenges of designing such studies given wound heterogeneity. Use of practice based evidence (PBE) and observational study data can provide important clinical insights that are generally missing from RCTs [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%